CLINICAL EVALUATION OF RUBRIC MENOPAUSE THROUGH MENOPAUSE RATING SCALE (M.R.S) WITH THE HELP OF CROSS REPERTORIZATION FROM KENT, MURPHY AND BOERICKE REPERTORY. (CAHIERS MAGELLANES-NS, 2024)
Menopause is “complete cessation of menstrual periods”. It is not a disease but a transitional state of women. As women age, their health becomes a multidimensional issue influenced by factors such as career, changes in home life, diet and physical activity, the economy, society and the environment. Though menopause is a normal physiological change, yet we find majority of females undergo a many of symptoms in varying intensity, which can be termed as a “Menopausal syndrome”.Background: Women generally experience menopausal distress during the change of their life also known as the climacteric year’s i.e. between the ages of 45 to 55 years. Homoeopathic treatment is gentle and harmless without causing any side effect.